The Effect of Learning Model and Intelligence Quotient on Critical Thinking and Handball Games Performance - Juliantine, Tite; Arifin, Fitriane (Universitas Pendidikan Indonesia, 2019)
Teaching physical education in schools today is still based on the delivery of the games movement and sports information, so that the cognitive ability, reflective-critical thinking skills, and students’ performance have not fully developed yet. The purpose of this study was to discover the reflective cognitive development of critical thinking abilities and the performance in playing handball in physical education classes. Its used 2x2 factorial design conducted on 74 students of grade Sernior High School in Bandung. Instrument used to measure the ability of critical thinking was the test to measure the critical thinking ability, while GPAI was used to measure games performance. The study shows that there is a significant effect of the critical thinking skills inquiry learning model treatment, whereas the direct treatment shows that there is a significant influence on the performance in playing handball. The results also discover the interaction in intelligence quotient and learning model and both of the models have influence on the students who have high and low intelligence. AbstrakPengajaran pendidikan jasmani di sekolah masih berlandaskan pada penyampaian informasi gerak permainan atau olahraga semata, sehingga kemampuan kognitif reflektif-kemampuan berpikir kritis dan penampilan bermain siswa belum berkembang. Tujuan penelitian ini adalah untuk menelurusi kebenaran pengembangan kognitif reflektif-kemampuan berpikir kritis dan penampilan bermain bola tangan dalam pembelajaran pendidikan jasmani.Penelitian ini menggunakan desain faktorial 2x2 dilakukan pada 74 orang siswa kelas SMA di Bandung. Instrument yang digunakan untuk mengukur kemampuan berpikir kritis yaitu dengan tes kemampuan berpikir kritis sedangkan GPAI untuk mengukur keterampilan bermain. Hasil penelitian menyimpulkan bahwa terdapat pengaruh signifikan kemampuan berpikir kritis dari perlakuan model pembelajaran inkuiri, sedangkan pada perlakuan direct teaching menyatakan pula terdapat pengaruh signifikan penampilan bermain bola tangan. Hasil penelitian selanjutnya model pembelajaran dengan intelligence quotient terdapat interaksi dan kedua model tersebut mempengaruhi pada tingkat siswa yang memiliki intelligence tinggi daan rendah.